Manchas foliares de alternária e septória em girassol: modelagem da severidade e redução da produtividade - Brand, Silvane Isabel (2017)
The objective of this work was to evaluate the progression of the disease under different leaf wetness with adjustment of an agrometeorological forecasting system of the septoria spot on the sunflower based on meteorological variables, in two experiments, in the central RS region. In addition, the objective of this study was to evaluate the effect of alternaria and septoria leaf spot, Area under the Disease Progression Curve (AACPD) and Duration of Healthy Foliar Area (DAFS) on the productivity of sunflower in years under different meteorological conditions in the central region of RS. The experiments were conducted under partially controlled conditions of artificial leaf wetting applied by microaspersion above the sunflower plants. The eight treatments consisted of: one control without leaf wetting and seven treatments with artificial wetting times (8 h, 12 h, 16 h, 20 h, 24 h, 28 h and 32 h). The experimental design was completely randomized, with four replications. Each plot was composed of 60 plants spaced 0.33 m apart in the row and 0.7 m between rows. Inoculation with Septoria helianthi was carried out in the reproductive stage. In all the experimental plots, severity (SEV) and incidence of septoria spot were evaluated every two days and phenological and phenometric observations on a weekly basis. AACPD and DAFS were also calculated. The forecast models were adjusted according to the meteorological variables, daily average air temperature, daily average relative air humidity and accumulated daily rainfall. With the data of SEV, AACPD and DAFS, it was performed the regression analysis and function adjustment and evaluation of the statistical parameters. It was also evaluated the growth patterns of the septoria leaf spot, monito, logito and gompito, in the different leaf wetness. With the severity data estimated by the model it was performed the correlation with the observed severity, with evaluation of the statistical parameters. Harvesting and threshing of 10 capitulum per plot was performed and productivity components were evaluated. For the analysis of the 25 experiments carried out in different years, it was evaluated the alternaria and septoria leaf spot and the effect of crop productivity and the relationship with SEV, AACPD and DAFS through the use of maximum limit graphs. In the January experiment, the severity and AACPD were higher than that of the November experiment, the opposite being observed for the DAFS. The prediction system in both experiments presented a good adjustament, with a coefficient of determination ranging from 0.95 to 0.99, and the adjustament was better in the January experiment. The septoria leaf spot promoted a reduction in productivity of up to 95%, but was only statistically significant in the January experiment. The growth pattern of the septoria leaf spot that adjustment most of the additional wetting was the logito model. The severity of up to 24% does not result in a decrease in productivity, after which increases of 1% in SEV results in a reduction of 69 kg ha-1 in sunflower productivity. Addition in AACPD also results in decreased sunflower productivity. With DAFS of 100, the highest sunflower productivity occurs.